2008
DOI: 10.1590/s0073-47212008000200017
|View full text |Cite
|
Sign up to set email alerts
|

Ecologia de duas espécies de Pachyurus (Perciformes, Sciaenidae) do rio Tocantins, na região represada pela UHE Serra da Mesa, Goiás

Abstract: ABSTRACT. Ecology of two species of Pachyurus (Perciformes, Sciaenidae) from the Tocantins River, in the region impounded by the Serra da Mesa hydroelectric dam, Goiás. Pachyurus schomburgkii Günther, 1860 and P. paucirastrus Aguilera, 1983 occur in the Tocantins-Araguaia basin, where the latter is endemic. The species were found in the upper Tocantins, in the region where it was impounded by the Serra da Mesa hydroelectric dam. Fourteen sites were sampled but both species were restricted to two sites (FU and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
1
6
0
2
Order By: Relevance
“…The main items found by Fugi et al (2007) were also the most important ones here, however two others insect orders were also important: Odonata and Trichoptera. Pacheco et al (2008) also found an insectivorous diet for P. schomburgkii Gunther, 1860 andP. paucirastrus Aguilera, 1983.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…The main items found by Fugi et al (2007) were also the most important ones here, however two others insect orders were also important: Odonata and Trichoptera. Pacheco et al (2008) also found an insectivorous diet for P. schomburgkii Gunther, 1860 andP. paucirastrus Aguilera, 1983.…”
Section: Discussionmentioning
confidence: 90%
“…paucirastrus Aguilera, 1983. The predominance of aquatic insects in the food of fish is common in freshwater communities (Sabino and Castro, 1990;Aranha et al, 2000;Abes et al, 2001;Andrade and Braga, 2005;Pouilly et al, 2004;Braga, 2005;Fugi et al, 2007;Pacheco et al, 2008), making the insect larvae a very important food category for fish (Zavala-Camin, 1996). Certain benthic insects, such as Diptera larvae and Ephemeroptera, are abundant in rivers with sandy bottoms (Braga, 2005) such as the Ibicuí River.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations